Crystallization Behavior and Anti-Leaching Performance of Iron Phosphate Glass Solidified Wasteforms Containing Ca3(PO4)2 Simulated Waste - Lin ZHANG; Jiong CHANG; Ming-shuai YANG; Jia-teng WANG; Sheng-heng TAN; Hui HE (He huaxue yu fangshe huaxue)
Radioactive TBP/OK organic liquid waste is generated during the processes of uranium purification and spent fuel reprocessing. After high-temperature oxidation treatment, the main products of this waste liquid are calcium phosphate and pyrophosphate. The waste also contains volatile radioactive nuclides such as cesium, as well as alpha-emitting nuclides like uranium(U) and plutonium(Pu). If discharged directly or improperly treated, this waste liquid may cause radioactive environmental pollution, which can severely impact ecological health and human health. Therefore, it is essential to use appropriate methods to solidify the cracked products to safely manage and dispose of the secondary waste generated from TBP cracking. Borosilicate glass shows limited tolerance for waste containing large amounts of phosphates, iron oxides, and some heavy metal nuclides(such as La, U, and Bi). In recent years, iron phosphate glass has attracted widespread attention and in-depth research due to its good tolerance for phosphates, sulfates, iron oxides, and other heavy metal elements in high-level radioactive waste, as well as its good stability. The O-P-O bonds in the structure of iron phosphate glass are replaced by more stable Fe-P-O bonds, resulting in a large number of stable Fe-P-O bonds in the glass. Additionally, iron phosphate glass has a lower melting temperature. In this study, a quaternary iron phosphate glass with the composition (37−x)(mole fraction, %, the same below)Fe2O3-xB2O3-56P2O5-7Na2O was used as the vitrification matrix to conduct glass solidification experiments on simulated waste. The experiments investigated the effects of different simulated waste contents and varying B2O3 contents on the crystallization behavior and chemical stability of the iron phosphate glass solidified bodies. Through comprehensive analysis using X-ray diffraction(XRD), differential thermal analysis, and scanning electron microscopy-energy dispersive X-ray spectroscopy(SEM-EDS), it was found that this formulation can tolerate up to 35%(mass fraction, the same below) of waste. The results show that in the (37−x)Fe2O3-xB2O3-56P2O5-7Na2O, when the B2O3 mole fraction is between 0 and 3%, the glass solidified bodies exhibit significantly worse crystallization tendency, density, homogeneity of the glass phase, and leaching of related elements compared to those with a B2O3 mole fraction of 5% to 10%. The PCT-B leaching test results indicate that when the waste loading is 30%, as the B2O3 mole fraction increases, the normalized quality losses of P, B, Cs, Na, and Ca are on the order of 10−5 g/m2; the normalized quality losses of Sr is on the order of 10−6 g/m2; and the normalized quality losses of La is on the order of 10−7 g/m2. The normalized quality losses relationship is as follows: NLP, B, Cs, Na, Ca\begin{document}$\gg $\end{document}NLSr\begin{document}$\gg $\end{document}NLLa\begin{document}$\gg $\end{document}NLFe. The normalized quality losses of all elements are less than 10−2 g/m2. Moreover, as the B content in the system increases, both the glass transition temperature(Tg) and the liquidus temperature(Tc) show an upward trend, indicating that the glass structure is enhanced, the density is increased, and the chemical stability is improved. Therefore, this formulation can be used as a suitable glass solidification formulation for simulated oxide products.